Awesome yo-yo tricks - Levine, Shar, 1953-; Bowden, Bob, 1954- (New York : Sterling Pub. Co., 2000)
Presents the history of the yo-yo and describes the basic techniques involve in simple, intermediate, and advanced tricks.
Includes index.
Keywords: Yo-yos -- Juvenile literature; Yo-yos.